PROGRESSIVE DECISION MAKING IN THE DEPARTMENT OF CARDIOLOGY BY OPTIMIZED ROUGH SET MODEL - VIDYULLATHA PELLAKURI,; D.RAJESWARA RAO, (International Journal of Pharma and Bio Sciences, 2016)
Decision making is becoming a versatile field of research in healthcare environment. Physicians have to recommend the type of treatment before making decision whether the patient has the particular disease or not. Patients life expectancy also increases with the right decision and treatment recommended by the physicians. To reduce the diagnosis time and enhance the diagnosis accuracy, it has become more of a challenging issue to develop reliable and powerful medical decision support systems. All of these decisions will guide the physicians and improve the health of the patients. In this paper, Rough set theory is applied to reduce the uncertainty attributes and redundancy objects of heart data and to find the core attributes for decision making in the department of cardiology.